THEORETICAL BASIS OF USING CORRELATION COEFFICIENTS IN MARKETING RESEARCH (Marketing Journal, 2025)
The article discusses the theoretical foundations of correlation coefficients used to assess the relationships between variables in marketing research. Pearson, Spearman, and Kendall coefficients, as well as more complex forms of correlation (nonlinear and partial correlation), are explained using marketing indicators such as demand, price, advertising effectiveness, and consumer behavior.
Keywords: relationship; Pearson; Spearman; Kendall coefficients; advertising; marketing; brand image